L’Église, les fidèles et la mort, à travers des miracles de saint Dominique (Rouen, 1261-1271) - Mathilde Cordonnier (Tabularia)
In the XIIIth century there were miracles in Rouen allegedly caused by saint Dominic’s relics. They were related in Miracula. The former are particularly interesting when it comes to studying the connection between writing and the dead in the Middle Ages, both for their content and their use. Indeed, the ubiquity of death in these Miracula emphasises the strong grip of the Church, whether it be through sacraments, religious brotherhoods, the cult of saints or preaching.